Giorgio Agamben: a condição da vida humana no Estado de exceção - Pacífico, Amanda Cristina (2018)
The purpose of this work is to analyze, from the thought of the Italian philosopher Giorgio Agamben, the phenomenon of the State of exception. The purpose of our investigation is to analyze the following question: How does the state of exception become the paradigm of government in the condition of human life, of modern societies? For Giorgio Agamben, the state of exception is the governance paradigm of contemporaneity, with the exception being the founding paradigm of the Modern State, both in the totalitarian or democratic version. At first glance, we can say that the state of exception is the original device by which sovereign power captures human life. Agamben captures a simultaneous tension in politics and law, in his relation to human life. The general objective of this research is to analyze the categories of bare life, device and sovereignty, according to the philosopher, terms present in the definition of the state of exception. Our bibliographic research begins with the works of Giorgio Agamben, belonging to his philosophical project called HOMO SACER, specifically the State of Exception work, object of our investigation. Initially, we articulate the path used by the philosopher in understanding the denomination of the State of exception. Based on this research, we describe the polarity between the democratic rule of law and the state of exception, by addressing the following hypothesis: the democratic state of law as a state of exception and the state of exception as a rule. Our intention is, from this research, to contribute to the debates of the political philosophy and the philosophy of the right about this object.